Thermodynamic efficiency of the cardiac cycle and irreversibility in the interbeat interval time series - Muñoz Diosdado, Alejandro; Gálvez Coyt, Gonzalo; Martínez, Alejandro Alonso (Revista Mexicana de Ingenieria Biomedica, 2018)
Cardiac cycle can be analyzed as a thermodynamic cycle, however, the inherent variability of this cycle implies that, although in the short term the cycle is quasi-reversible, in the long term is irreversible. This work discusses two important aspects of the cardiac cycle related with thermodynamic concepts: the calculation of the cycle’s efficiency and the quantification of the irreversibility of interbeat interval time series. The results show that there is a variability of cardiac efficiency along the day for both healthy and congestive heart failure (CHF) patients, and there is a substantial reduction in efficiency for CHF patients. If time reversibility on different scales is taken into account, methods as spectral power, fractal dimension and detrended fluctuation analysis (DFA) give the same results, but if the analysis is performed with the multiscale time irreversibility method applied to the interbeat interval time series, it results that the interbeat interval time series of healthy persons are irreversible and time series of CHF patients tend to reversibility.